2009
DOI: 10.1002/anie.200902236
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cross‐Couplings with Part‐per‐Million Catalyst Loadings

Abstract: Due to the importance of functionalized arenes as scaffolds in applied organic materials and biologically relevant molecules, metal-catalyzed cross-couplings have gained significant attention in recent years. [1,2] Among them Ullmann type CÀX bond formations are particularly attractive because they often allow the use of low-cost starting materials in combination with readily available copper salts.[2] Whereas the initial protocols [3] required high temperatures and over-stoichiometric quantities of metal, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(62 citation statements)
references
References 70 publications
(3 reference statements)
4
55
1
2
Order By: Relevance
“…Although Nageswar and co-workers state that > 99.9% La 2 O 3 is utilized in these reactions, Bolm and Buchwald have shown that the presence of only ppm levels of copper can effectively catalyze these reactions. [7,12] Further, several of the observations made in this paper are consistent with the hypothesis that the active catalyst is copper-based. [5] First, the best ligand for the reported transformation (DMEDA) is also the best ligand for these reactions using a copper-based system.…”
supporting
confidence: 88%
“…Although Nageswar and co-workers state that > 99.9% La 2 O 3 is utilized in these reactions, Bolm and Buchwald have shown that the presence of only ppm levels of copper can effectively catalyze these reactions. [7,12] Further, several of the observations made in this paper are consistent with the hypothesis that the active catalyst is copper-based. [5] First, the best ligand for the reported transformation (DMEDA) is also the best ligand for these reactions using a copper-based system.…”
supporting
confidence: 88%
“…In contrast to ref. 17, we could not show activity for Cu 2+ species in our reaction sequence. All used Cu(II) salts (Cu(NO 3 ) 2 , CuSO 4 , CuCl 2 , Cu(OAc) 2 and CuF 2 ) failed completely in catalysing the amination of iodobenzene with ammonia under the same conditions.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 55%
“…[12][13][14] Homogeneously driven copper(I) catalysed C-N bond formation sometimes requires only homeopathic catalyst loadings, but the use of ligands, base or other additives as well as inert conditions are usually necessary. [15][16][17] Heterogeneous C-N cross coupling catalysed by copper(I) requires rather harsh reaction conditions but does not need ligands and shows a good reaction workup. 18,19 However, up to now nanoscale copper(I) catalysed cross coupling reactions, especially C-N bond formation, have rarely been reported in scientific literature 13,[20][21][22] or show drawbacks in versatility and catalyst loadings.…”
Section: Introductionmentioning
confidence: 99%
“…However, current methods have some potential limitations because these transformations often use expensive transition-metal catalyst as palladium [9], rhodium [10], nickel [11], and cobalt [12] complexes. Thus, screening out inexpensive and environmentally benign metal catalysts for the N-arylation of azoles still remains a great challenge [13]. Inexpensive copper catalysts bearing various ligands provided a highly economical and efficient method for N-arylation of nitrogen-containing heterocycles with aryl halides.…”
Section: Introductionmentioning
confidence: 99%